Extent of Parental School Involvement on Pupils’ Academic Performance in Anambra State, Nigeria - J.O. Enemuo; C .Y. Onyenwe (BIRCU, 2020)
This study was carried out to investigate the extent of parental-school involvement on pupils’ academic performance in Anambra State. Four research questions and four null hypotheses guided the study. It adopted a descriptive survey research design. Two research questions guided the study. The population of the study consisted of 10,369 primary school teachers and 65,406 parents in Anambra state. The sample size for the study comprised of 736 which made up of 172 primary school teachers and 564 parents whose children/wards are in primary schools in Awka North, Awka south, Anambra, Dunukofia and Njikoka local Government Education Authorities were selected using multi-stage sampling. Data were collected using two structured questionnaires titled “Teachers Response on Parental School Involvement Questionnaire (TRPSIQ) and parent’s response on school involvement questionnaire (PRSIQ). The TRPSIQ and PRSIQ was validated by three experts. The reliability of the instrument was determined using Cronbach Alpha which yielded an overall co-efficient of 0.83. mean was used to answer the research questions while standard deviation was used to check the closeness of the respondent’s response to the mean. The findings revealed that teachers and parents rated to a great extent parental involvement in child home-school communication and school volunteering for improvement in pupil’s academic performance. Based on the findings, the researcher recommended among others that schools should create good communication language style that will foster close interaction between the parents and the child as well as the parents and the schools.